Nursing supervised curricular internship in the Covid-19 pandemic: experience in the program Brasil Conta Comigo - Souza, Lara Arcipreti Boel; Neves, Heliny Carneiro Cunha; Aredes, Natália Del Angelo; Medeiros, Isabel Cristina Lima Jobim; Silva, George Oliveira; Ribeiro, Luana Cássia Miranda (Revista da Escola de Enfermagem da USP, 2021)
Objective: To report the experience of the nursing supervised curricular internship in the program “O Brasil Conta Comigo” carried out in the Covid-19 pandemic. Method: Experience report of activities developed in Primary Health Care in a municipality in the southern region of the state of Goiás during the Covid-19 pandemic, from April to November 2020. Results: The inclusion in the government program allowed the strengthening of the student’s active role in the teaching-learning process and teaching-service approximation, with the student as the point of connection, which resulted in the implementation of actions for the fight against the pandemic in the municipality, such as elaboration, implementation, and evaluation of the service flowchart for people with suspected Covid-19. Conclusion: The experience was successful, as it consolidated knowledge regarding leadership and autonomy, integration between theory and practice, critical thinking, and evidence-based problem solving. The participation in the program allowed for contributions to assistance and management in the actions to combat the new coronavirus in the scope of primary care, as well as for the contribution to the training of the student tutored by nurses in the field and supervised by professors from the federal university of origin.